Complete Guide to Digital Project Management From Pre-Sales to Post-Production - Shivakumar, Shailesh Kumar (Apress, 2018)
Get a 360-degree view of digital project management. Learn proven best practices from case studies and real-world scenarios. A variety of project management tools, templates, models, and frameworks are covered. This book provides an in-depth view of digital project management from initiation to execution to monitoring and maintenance. Covering end-to-end topics from pre-sales to post-production, the book explores project management from various dimensions. Each core concept is complemented by case studies and real-world scenarios. The Complete Guide to Digital Project Management provides valuable tools for your use such as: Frameworks: governance, quality, knowledge transfer, root cause analysis, digital product evaluation, digital consulting, estimation Templates: estimation, staffing, resource induction, RACI Models: governance, estimation, pricing, digital maturity continuous execution, earned value management and effort forecast Metrics: project management, quality What You'll Learn: Study best practices and failure scenarios in digital projects, including common challenges, recurring problem themes, and leading indicators of project failures Explore an in-depth discussion of topics related to project quality and project governance Understand Agile and Scrum practices for Agile execution See how to apply Quality Management in digital projects, including a quality strategy, a quality framework, achieving quality in various project phases, and quality best practices Be able to use proven metrics and KPIs to track, monitor, and measure project performance Discover upcoming trends and innovations in digital project management Read more than 20 real-world scenarios in digital project management with proven best practices to handle the scenarios, and a chapter on a digital transformation case study.